Understanding the Decision-Making Process of Women to Engage in Cohabiting Relationships - Kgadima, Nathaniel Phuti; Leburu, Goitseone Emelda (International Journal of Criminology and Sociology, 2022)
Despite the extensive literature on cohabitation, there is scant literature that explores women’s decisions to engage in cohabitation. Drawing on the theory of planned behaviour and a qualitative research approach, this article explores the decision-making processes among women to engage in cohabitation. For some women, cohabitation was preceded by a clear conversation about the intention to marry. The second group of women described cohabitation as an expression of autonomy and independence by rejecting traditionally prescribed conventions such as marriage. When the promise of marriage fails to materialise, some women become increasingly disillusioned and opt to terminate their co-residence relationships in order to negotiate marriage as an option with their partners. This article utilised purposively and snowball sampling to gather data and this was through semi-structured interviews. This data was analysed thematically, and the results show a preponderance of a desire for autonomy that is checked by the harsh persistence of disempowering narratives. Further research is needed to establish patterns of autonomy in cohabiting partners.